2017
DOI: 10.5712/rbmfc12(39)1507
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients for palliative care in primary care in Brazil: Project Estar ao Seu Lado’s experience

Abstract: Identificando pacientes para cuidados paliativos na atenção primária no Brasil: experiência do Projeto Estar ao Seu Lado Objetivo: Apresentar o processo de identificação de pacientes de cuidados paliativos em uma equipe de Estratégia de Saúde da Família no Brasil. Métodos: O processo de identificação ocorreu 1) utilizando o sistema de trabalho de uma Equipe de Estratégia de Saúde da Família e os princípios da atenção primária e 2) aplicando o SPICT, uma ferramenta para ajudar a identificar pacientes que poderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
3
Order By: Relevance
“…In the research, a total of 154 studies were found, publications (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were relevant for this review, since they met the study question and pre-established criteria, as explained in the analysis flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the research, a total of 154 studies were found, publications (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were relevant for this review, since they met the study question and pre-established criteria, as explained in the analysis flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to language, eleven studies analyzed were published in Portuguese (9)(10)(11)(18)(19)(20)(21)(23)(24)(25)(26) and from Brazilian authors, five were published in Spanish (12)(13)(15)(16)(17) and three in English (14,16,22) . Of the included studies, eight (9)(10)(11)(17)(18)(19)(20)(21) used the qualitative approach and ten, the quantitative (12)(13)(14)(15)(16)(22)(23)(24)(25)(26) . As for the instruments / techniques for data collection/production, questionnaires, interviews, observation, discussion groups and application of scales were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our second editorial drew responses from family doctors around the world, saying that primary palliative care had a major role in palliative care delivery and strategy. Brazil is progressing rapidly in this field owing to a strong primary care programme 4. In Colorado, USA, the primary care system has service and policy barriers but strong advocates for palliative care 5.…”
mentioning
confidence: 99%
“…There is not a specific agenda or program for palliative care from the National Program of Primary Care called Family Health Strategy, despite its 43,000 active teams distributed around the country 10 covering over 60% of the population (around 168 million). Very few community centers provide systematic palliative care, too 11 , and there is no integrated network that supports and follows patients when identified as needing palliative care figure 1.…”
mentioning
confidence: 99%